2021
DOI: 10.3390/app11104397
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and Diabetes Mellitus: Biomarkers in Risk Stratification and Prognostication

Abstract: Heart failure (HF) and type 2 diabetes mellitus (T2DM) have a synergistic effect on cardiovascular (CV) morbidity and mortality in patients with established CV disease (CVD). The aim of this review is to summarize the knowledge regarding the discriminative abilities of conventional and novel biomarkers in T2DM patients with established HF or at higher risk of developing HF. While conventional biomarkers, such as natriuretic peptides and high-sensitivity troponins demonstrate high predictive ability in HF with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 201 publications
(225 reference statements)
0
3
0
Order By: Relevance
“…NT-proBNP are biomarkers that are released from the heart in response to inflammation, hypoxia, or myocardial stretching. They have been proved to be a useful marker for the prediction of the development of heart failure in patients with type 2 diabetes 15 . We found that Both drugs have significantly improved the level of NT-proBNP, these findings are contradicting with Kusunose et al, whose findings showed that the level of NT-proBNP was elevated with glimepiride, and are in accordance with Jariwala et al, whose findings have showed that NT-proBNP level is significantly reduced and improved with dapagliflozin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NT-proBNP are biomarkers that are released from the heart in response to inflammation, hypoxia, or myocardial stretching. They have been proved to be a useful marker for the prediction of the development of heart failure in patients with type 2 diabetes 15 . We found that Both drugs have significantly improved the level of NT-proBNP, these findings are contradicting with Kusunose et al, whose findings showed that the level of NT-proBNP was elevated with glimepiride, and are in accordance with Jariwala et al, whose findings have showed that NT-proBNP level is significantly reduced and improved with dapagliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…Serum level of NP is used as a diagnostic tool for heart failure (HF) development and risk of cardiovascular death, as their serum level increase with the development of heart failure. NP have markedly used in the prediction of incident HF and total cardiovascular events in patients with type 2 diabetes 15 . The ADVANCE trial has shown that NT-proBNP levels are powerful prediction tools for the risk of HF, and death from cardiovascular events in patients with type 2 diabetes mellitus 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation